Практична реалізація концепції корпораційної екологічної системи для інтегральної оцінки екологічного ризику здоров’ю - Kozulіa, T. V.; Sharonova, N. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Practical and theoretical fundamentals for the necessity and advisability of introduction of the corporative ecological system (CES) into the decision making system are prescuted. Mathematical approaches are defined to the determination, of interactions between the CES components, the ascertainment of breaking risk from the appearance of negative influence factor, and the introduction of health risk estimation as a danger criterion of a socioeconomic system. An algorithm of the CES state determination on the basis of health risk estimation is presented.